Quality of life: pre-and post-functional endoscopic sinus surgery in chronic rhinosinusitis - Poojitha, S.; Tanthry, Deepalakhmi; Santhraya G., Mahesh; P. P., Devan; Bhandary, Rukma; K. Pai, Vishwas; Kamath, Sanjana; Nehla, Aisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Chronic sinusitis (CRS) includes all inflammatory diseases of the nose and paranasal sinuses with a minimum duration of 12 weeks. Physical examination (anterior rhinoscopy, endoscopy) and/or radiography, ideally from sinus computed tomography, can provide objective proof of the same. After failure of conservative treatment, functional endoscopic sinus surgery (FESS) is the preferred modality for chronic rhinosinusitis that has been frequently used over the past years. Methods: The present prospective study aimed to assess the quality of life (QOL), the nasal endoscopy scores- before and after FESS in 60 patients aged more than 18 years suffering from chronic rhinosinusitis. QOL was assessed using SNOT-20 questionnaire and endoscopy was quantified using Lund-Kennedy sinonasal endoscopy scoring system. Results: QOL scores were significantly higher (p<0.001) before surgery (41.28±15.30) than after FESS (6.83±5.96) indicating improvement in QOL. Lund-Kennedy endoscopy scores of patients suffering from chronic rhinosinusitis before and after surgery was also significantly reduced (p<0.001). Conclusions: This study concludes that there is significant improvement in the QOL and reduction in the severity of symptoms in patients suffering from chronic rhinosinusitis after FESS.